Perbedaan jumlah kuman pada peralatan makan antara pencucian melalui perendaman dan air mengalir di Lampenerut Aceh Besar - Khairunnisa Khairunnisa; Budi Arianto (Politeknik Kesehatan Kemenkes Aceh, 2023)
Background: food contamination can be caused by various factors, including personal hygiene, food handler knowledge, food sanitation, and the cleanliness of cutlery. A microbiological examination that can be done is a swab of cooking utensils and cutlery, including a germ count examination. Germ found in cutlery will pose a health risk to consumers.Objectives: the purpose of this study was to determine the number of bacterial colonies found on cutlery between soaking washing and flowing water, using the TPC (Total Plate Count) method.Methods: observational research using a cross-sectional design. This type of research is observational with a descriptive design. This research was conducted in Lampenerut Aceh Besar in June 2022. This study used the total plate count method with data analyzed univariately and presented in tabular form. Statistical analysis using Independent T-test, the number of samples taken was 20 samples.Results: soaking washing found germs in all cutlery samples, with the highest number being 24 CFU/cm2. Flowing washing obtained 6 samples with a germ number of 0 CFU/cm2 in accordance with the regulation Permenkes RI No.1096 of 2011, while 14 samples contained germ with the highest number of 17 CFU/cm2. There is a difference in the number of germ in soaking washing and flowing water washing (p=0,000) on cutlery in Lampenerut Aceh Besar.Conclusion: the number of germs on cutlery washed with flowing water is lower than the number of germs in immersion washing. Trader and the public are advised to use the process of washing cutlery using flowing water, because it is proven to be more effective in reducing the number of germs.